2017
DOI: 10.1194/jlr.m073932
|View full text |Cite
|
Sign up to set email alerts
|

Assessing anesthetic activity through modulation of the membrane dipole potential

Abstract: There is great individual variation in response to general anesthetics (GAs) leading to difficulties in optimal dosing and sometimes even accidental awareness during general anesthesia (AAGA). AAGA is a rare, but potentially devastating, complication affecting between 0.1% and 2% of patients undergoing surgery. The development of novel personalized screening techniques to accurately predict a patient’s response to GAs and the risk of AAGA remains an unmet clinical need. In the present study, we demonstrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 106 publications
(141 reference statements)
0
5
0
Order By: Relevance
“…The figure shows a reduction in R of ∼16% at the highest concentration of PEtOH used. Although general anesthetics have previously been shown to reduce membrane dipole potential, to the best of our knowledge, our results constitute the first experimental report of reduction in membrane dipole potential by a local anesthetic.…”
Section: Resultsmentioning
confidence: 57%
“…The figure shows a reduction in R of ∼16% at the highest concentration of PEtOH used. Although general anesthetics have previously been shown to reduce membrane dipole potential, to the best of our knowledge, our results constitute the first experimental report of reduction in membrane dipole potential by a local anesthetic.…”
Section: Resultsmentioning
confidence: 57%
“…16 NA V CHANNELS AND LIPID RAFTS AS ANESTHETIC TARGETS Anesthetics enter cells through the membrane due to their lipid solubility and alter Na V function through different mechanisms. These mechanisms can include changes in lipid membrane properties such as variations in fluidity, permeability, or dipole potential, 121,124,125 affinities for different functional states of ion channels, 126 pore blockage, 127 binding or altering the selectivity filter of ion channels, 82 and modification of the inactivation state (Table ). 128 General anesthetics have low affinity and high exchange rates 82 which gives them nonspecific membrane-mediated action mechanisms.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…Selectivity filter near DEKA motif, voltage-sensing linker (S4-S5) on DI, DIII, and DIV that may alter affinities for different functional states of the ion channel, fenestrations within the pore (particularly DIV), causing blockage using a charged residue 81,126 ; Extracellular site near selectivity filter in DIV (activation gate) 79,134 Increases diameter, area, and number of lipid rafts, increases PLD2 activity, altering membrane ion permeability, PLD2 translocates away from lipid rafts, enhancing PIP 2 regulation 25,62 ; Increases lipid lateral mobility and reduces mechanical stiffness of the plasma membrane 135 ; reduces sterolphospholipid association in L o domains 120 ; reduces membrane dipole potential 125…”
Section: Inhalationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Table shows a comprehensive list of membrane proteins (and peptides) whose functions are known to be affected by a change in membrane dipole potential. In addition, dipole potential is sensitive to interaction of proteins with membrane. ,, Interestingly, the action of anesthetics has been shown to be via modulation of membrane dipole potential. , It has also been suggested that local dipole potential could play an important role in the function of proteins localized to specialized membrane microdomains, where the dipole potential is different from the bulk membrane due to the enrichment of cholesterol in these domains. , …”
Section: Functional Implications Of Membrane Dipole Potentialmentioning
confidence: 99%